A late Quaternary vertebrate deposit in Kudjal Yolgah Cave, south‐western Australia: refining regional late Pleistocene extinctions. (14th July 2016) - Jankowski, Nathan R.; Gully, Grant A.; Jacobs, Zenobia; Roberts, Richard G.; Prideaux, Gavin J.
ABSTRACT: We describe the stratigraphy and chronology of Kudjal Yolgah Cave in south‐western Australia, a late Quaternary deposit pre‐ and post‐dating regional human arrival and preserving fossils of extinct and extant fauna. Single‐grain optically stimulated luminescence (OSL) dating shows that seven superposed units were deposited over the past 80 ka. Remains of 16 mammal species have been found at the site, all of them represented in Unit 7, for which seven OSL ages indicate accumulation between 80 and 41 ka. Single‐grain OSL equivalent dose distribution patterns show no evidence of reworking of older or younger sediments into Unit 7, but late Holocene charcoal has been washed into the top of it from adjacent Unit 2, deposited 1.2 ka ago. Six species that failed to survive the Pleistocene are recorded in Unit 7, but only the south‐western wombat Vombatus hacketti is recorded in younger units. Two species, the large extinct kangaroos Protemnodon sp. cf . P. roechus and Procoptodon browneorum, are represented by articulated specimens near the top of Unit 7, immediately adjacent to an OSL sediment sample dated to 41 ± 2 ka. These are the youngest reliably dated records of these genera from mainland Australia, and among the youngest megafaunal remains from the continent. All species currently known from the middle Pleistocene of the south‐west persisted into the late Pleistocene, which removes a key pillar supporting the argument against a driving role for human impacts in the extinctions.